DETERMINING THE NECESSITY OF LAW OF NATIONS IN NATION-BUILDING: ADDRESSING THE PECULIARITIES OF THE EMERGING NATIONS (IUS LAW Journal, 2025)
The growing significance of the law of nations in nation building and the compelling need to address the peculiarities of emerging societies have led to rigorous efforts aimed at regulating institutions of international relations. This paper explores some of the challenges arising from different ratification of treaties, divergent interpretations of shared obligations and the recent wave of globalization and its impact on all aspects of global existence. It is against the backdrop driven by the desire to create stability in nation-building that law of nations system evolved. In this light, it becomes imperative that law of nations should be seen as a major driver in nation-building process. This is an important starting, point from which to reiterate the fact that nation-building cannot be guaranteed if the future of the law of nations are not taken into cognizance. It is argued that, the continued neglect of law of nations in nation-building process remained a clog in the development cooperation treaties. The paper adopted analytical and qualitative approach on current literatures, legislations and policies on the law of nations which is achieved by a synthesizing of ideas. Nevertheless, the paper concludes that in order to achieve nation-building agenda and the right to development through a legally-binding instruments.
Keywords: Law of Nations, Nation-Building, Necessity, Right to Development, Peculiarities